Voluntary corporate disclosure by companies listed on the Singapore Exchange (SGX). - Chong, Yew Tuck. (2008)
This paper seeks to investigate empirically the extent of voluntary disclosure in the 1998 annual reports of 100 companies listed on the Singapore Exchange, and the association between company's size, leverage, multiple stock exchange listing status, profitability, type of auditors employed, industry classification and ownership structure with voluntary disclosure level.